The role that cooperatives play in poverty alleviation : the case of Lepelle-Nkumpi local municipality - Bopape, Mahlogonolo Catherine (University of Limpopo, 2016)
This study examines the way cooperatives operate and particularly how these poverty alleviation projects impacts on poverty in Lepelle-Nkumpi Local Municipality (LNLM). The study also assessed the significance of government interventions contributing to the role the cooperatives play in alleviating poverty in LNLM. The research methodology used for this study involved both qualitative and quantitative research approaches. Data was collected using questionnaires whereby the researcher conducted one-on-one interviews to administer them. The interviewees were composed of officials from the three spheres of government and the members of the cooperatives in the chosen area of study. The various international and local literatures relating to cooperatives were reviewed. The key findings of this study revealed that cooperative enterprises in the municipality can alleviate poverty especially leveraging on interventions, such as training, specific funding and skills development for the cooperatives which will assist the cooperative to grow and to be more sustainable. It has also shown that members in cooperatives have been able to support their families to meet their basic needs despite the pressing conditions under which cooperatives operate. Some of the key recommendations proposed include: firstly, that government should create awareness amongst cooperatives on what are the national funding,and how this funding operates; secondly, that government should market the funding opportunities and clearly explain to the cooperatives how the schemes work and how they will assist in the operations of the cooperatives in order to avoid misconceptions; and thirdly and most importantly, the monitoring and evaluation by the state on cooperatives funding programmes should be conducted on a regular basis.
Thesis (M. Dev. (Development Studies)) -- University of Limpopo, 2016
Keywords: Cooperatives; Poverty alleviation; Lepelle-Nkumbi Local Municipality; Poverty -- South Africa